Pembinaan Karakter Religius Siswa Melalui Pembiasaan Shalawat Nariyah - M.Kharis Maulana; Anggraeni, Dewi (Mozaic : Islam Nusantara, 2025)
In the disruption era, strengthening religious character is very important to face various challenges, especially related to religious character education. One of the effective methods in fostering the character of students is through habituation of religious activities such as reading Shalawat Nariyah. This study aims to analyze the process, impact in fostering religious character through habituation of Shalawat Nariyah at MA Salafiyah Simbangkulon Buaran Pekalongan. The method used is a qualitative approach with descriptive research type, with the research location at MA Salafiyah Simbangkulon Buaran Pekalongan. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study show: 1) The habituation process includes giving diplomas, routine habituation, and implementing activities is considered an effective method in fostering student character. 2) There are changes in students' religiosity after practicing Shalawat Nariyah which includes religious indicators such as obeying Allah, gratitude, sincerity, patience, and tawakal. Positive changes in student attitudes are inseparable from the involvement and guidance of educators.